Management and Outcomes of Spontaneous Cerebrospinal Fluid Otorrhoea - Thomeer, Hans GXM; Schreurs, Corine; van Doormaal, Tristan PC; Straatman, Louise V. (Frontiers in Surgery, 2020)
Objective: A cohort of patients with spontaneous cerebrospinal fluid (sCSF) otorrhoea. To report surgical outcome and discuss a treatment protocol. Materials and Methods: Between 2012 and 2018 all patients presenting with sCSF were collected and data assessment was performed including clinical symptoms (hearing loss, aural fullness, meningitis, recurrent otitis media), preoperative audiometry, CT and MRI scanning. According to the site and size of the dural defect, different surgical approaches were applied. Results: A total of 12 patients (14 operations) were included. Four of these had a history of meningitis. All beta-trace protein testings were positive. These patients were treated with different surgical approaches: middle fossa approach (MCF, seven patients), transmastoid approach (TMA) with bony obliteration of the cavity (three patients), and four patients underwent a subtotal petrosectomy (STP) procedure. Three cases underwent revision surgery (MCF or STP) due to residual disease (CFS leakage). After follow up duration of 13 months (6.5 months SD), no recurrence was observed. No severe adverse events such as cerebrovascular injury, meningitis, wound infection, or headache was observed in the postoperative course. Conclusion: Spontaneous aural cerebrospinal fluid leakage is a rare but manageable pathology with potential severe complications. Appropriate diagnosis, laboratory testing, and imaging is primordial to obtain optimal patient outcome.